Efforts To Improve Learning Interest In Local Hero Woman - Septia Landa, Klara; Kamarubiani, Nike; Hasanah, Viena Rusmiati (Bisma The Journal of Counseling, 2022)
This study aims to determine the efforts to increase interest in learning in local hero of women at PKBM An-nur Ibun, Bandung. The method used in this research is descriptive qualitative. The   data was collected using direct interview, observation, and documentation techniques. The data obtained were then analyzed by data collection procedures, data reduction, data presentation, data interpretation, and data inference. The results of this study are to develop ideas, stimulate citizens to learn, meet great people, positive attitude. This can be seen from the enthusiasm in conveying ideas, the experience increases and develops, changes in opinion, behavior, mindset, ethics, good manners in the family and the community, benefits themselves and others, and adds insight.